A Flute, Musical Bows and Bamboo Clarinets that “Speak” in the Amazon Rainforest; Speech and Music in the Gavião Language of Rondônia - Meyer, Julien; Moore, Denny (Frontiers in Psychology, 2021)
The Gavião, a native Amazonian group in Rondônia, Brazil, use three different traditional musical instruments that they identify as “speaking” ones and that are characterized by a very tight music-lyric relation through similar pitch patterns: a flute (called kotiráp), a pair of mouth bows (iridináp), and three large bamboo clarinets (totoráp), played by three different players, each one playing a single-note clarinet). They show in different ways the relation of acoustic iconicity which exists between the words of the songs’ lyrics and the music played on such instruments to “sing” the songs. Linguistic analysis makes it possible to understand the phonetic and phonological nature of the iconicity. The sung speech form, being intermediate between the spoken and the instrumental forms, is useful for both learning and explaining the musical notes. In a language with distinctive tone and length, such as Gavião of Rondônia, the first question about speech that is played by musical instruments is the relation between the melodies and the super-segmental phonology of the corresponding words in sung speech and in modal spoken speech. It is influenced by the phonological possibilities of the spoken form and by the musical possibilities of the instrumental form. The description and analysis of Gavião instrumental speech and song practices are found to be a noteworthy contribution to the typology of instrumental language surrogates associated with a tone language, one that calls for a reexamination of hypotheses about which aspects of the phonological/phonetic structure can be transposed in instrumental speech and how this can be done. The role of this kind of instrumental sung speech is artistic and also practical as it contributes to maintain the oral heritage. Such practice represents a little-studied and threatened cultural heritage of the traditional substratum of the cultures of Amazonia.